The The Developing Global Employability Competencies of Indonesian Seafarers for Enhanced End-User Acceptance through Brand Experiences - Ayub Dwi Pranata Junus; Prijono Tjiptoherijanto; Nurdin Sobari; Athor Subroto (Universitas Pendidikan Ganesha, 2023)
The growth of global demand for qualified Indonesian seafarer labor is a key issue in this study. This study aims to analyze the impact of global work competencies and the mediating role of sensory, behavioral, and intellectual experiences in accepting end users in crew management companies. The study involved 240 crew managers/supervisors who interacted with Indonesian seafarers. The analysis was carried out using the Partial Least Square-Structural Equation Method. Research findings show that global work competencies have a significant effect on end-user acceptance. Nonetheless, sensory experience does not mediate the relationship between global work competence and end-user acceptance. In contrast, behavioral and intellectual experience play a key role as mediators, with intellectual experience having a more prominent impact than behavioral experience in increasing end-user acceptance. The conclusion of this study emphasizes the importance of global work competence and intellectual experience in increasing end-user acceptance in the context of crew management. The implications of this research support the development of global work competency development strategies to improve service quality in the shipping industry.